2010
DOI: 10.1093/aob/mcq030
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine under deficit irrigation: hints from physiological and molecular data

Abstract: How the whole plant acclimatizes to water scarcity and how short- and long-distance chemical and hydraulic signals intervene are reviewed. Chemical compounds synthesized in drying roots are shown to act as long-distance signals inducing leaf stomatal closure and/or restricting leaf growth. This explains why some plants endure soil drying without significant changes in shoot water status. The control of plant water potential by stomatal aperture via feed-forward mechanisms is associated with 'isohydric' behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
572
4
30

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(641 citation statements)
references
References 187 publications
(251 reference statements)
35
572
4
30
Order By: Relevance
“…Asterisks indicate significance differences between conditions (Student's t test; P < 0.01). (Castellarin et al, 2007a(Castellarin et al, , 2007bChaves et al, 2010). Thorough analysis revealed that anthocyanin biosynthesis is regulated by a transcriptional complex that is well conserved in different plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Asterisks indicate significance differences between conditions (Student's t test; P < 0.01). (Castellarin et al, 2007a(Castellarin et al, , 2007bChaves et al, 2010). Thorough analysis revealed that anthocyanin biosynthesis is regulated by a transcriptional complex that is well conserved in different plant species.…”
Section: Discussionmentioning
confidence: 99%
“…During the last three decades, more frequent episodes of drought stress and their intensity required the incorporation of water by irrigation as a way to overcome such limitation and to secure more regular and predictable yields (Chaves et al , 2010Flexas et al 2010). However, two considerations need to be taken in account when irrigating grapevines: (i) water requirements are usually high in semi-arid areas thus potentially compromising water resources and sustainability of agricultural practices (FAO 2014) and (ii) yield increases are commonly associated to grape quality reductions, since grape quality usually decreases in response to an excess of vigor creating an unbalance between the reproductive and vegetative organs within plants (Bravdo et al 1985;Dokoozlian and Kliewer 1996;Esteban et al 2001;Matthews et al 1990;McCarthy 1997).…”
Section: Deficit Irrigation Partial Root Irrigation or Partial Rootmentioning
confidence: 99%
“…In consequence, an important volume of applied and fundamental research has been focused into the exploration of the capacity to optimize grapevine water use. An important part of these researches are related to the evaluation of irrigation timing and schedule by introducing new technologies to reduce water consumption (Chaves et al 2010;Romero et al 2010;Sadras 2009;Williams et al 2010). Regarding the improvement of genetic capacities to enhance WUE, some works have been focused on the estimation of the genetic variation of grapevine rootstocks or cultivars (Alsina et al 2007;Satisha et al 2006;Tomás et al 2012).…”
Section: General Introductionmentioning
confidence: 99%
“…UV-B is not only potentially harmful, but it also serves as an environmental information source, though information about it is still scarce. As general abiotic stresses have been extensively reviewed [119][120][121][122][123][124][125], we will have special focus on UV-B-mediated perception and signalling responses of grapevine and photobiotechnological approaches to improve fruit quality for winemaking.…”
Section: Grapevine Abiotic Stressmentioning
confidence: 99%